2019
DOI: 10.5664/jcsm.7918
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Blink Parameters Detect On-Road Track-Driving Impairment Following Severe Sleep Deprivation

Abstract: Study Objectives: Drowsiness leads to 20% of fatal road crashes, while inability to assess drowsiness has hampered drowsiness interventions. This study examined the accuracy of eye-blink parameters for detecting drowsiness related driving impairment in real time. Methods: Twelve participants undertook two sessions of 2-hour track-driving in an instrumented vehicle following a normal night's sleep or 32 to 34 hours of extended wake in a randomized crossover design. Eye-blink parameters and lane excursion events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 65 publications
(113 reference statements)
0
25
0
Order By: Relevance
“…Despite ocular metrics being a strong indicator of drowsiness 35 , only the younger adults demonstrated increased ocular indices of drowsiness, including increased blink duration, LEC rate and PERCLOS during their sleep-deprived drive. Sleep loss related increases in ocular metrics have been well described in young drivers 14 , and are reliable and sensitive measures of drowsiness related driving impairment in younger drivers 36 . In contrast, in highly-controlled laboratory studies, older adults have shown a smaller increase in ocular ‘drowsy’ metrics and were less likely to fall asleep, consistent with our findings 11 .…”
Section: Discussionmentioning
confidence: 96%
“…Despite ocular metrics being a strong indicator of drowsiness 35 , only the younger adults demonstrated increased ocular indices of drowsiness, including increased blink duration, LEC rate and PERCLOS during their sleep-deprived drive. Sleep loss related increases in ocular metrics have been well described in young drivers 14 , and are reliable and sensitive measures of drowsiness related driving impairment in younger drivers 36 . In contrast, in highly-controlled laboratory studies, older adults have shown a smaller increase in ocular ‘drowsy’ metrics and were less likely to fall asleep, consistent with our findings 11 .…”
Section: Discussionmentioning
confidence: 96%
“…Incomplete blinking has been reported as an important marker of ocular symptoms during reading on smartphone and computer [9, 11, 77] and also during driving [82]. Future studies using the wearable eye tracker will enable examination of blink amplitude in situ during various task and conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The energy features of individual brain waves can thus be obtained.Omerbodzic et al [16] have verified that the EEG of epileptic patients can be classified by using energy signals in the time domain, and Zhong et al [17] have validated this in a large number of classification models using a public data set and obtained results ranging from 60.50% to 94.24% with different classification accuracies, further demonstrating that that energy features using EEG signals can be treated as task features for classification.…”
Section: Analysis Of Research Status and Development Trends At Home A...mentioning
confidence: 95%